Fluorine-containing polyamphiphiles of block structure constructed of synthetic and biopolymer blocks - Paiuk, O.L.; Mitina, N.Ye.; Myagkota, O.S.; Volianiuk, K.A.; Musat, N.; Stryganyuk, G.Z.; Reshetnyak, O.V.; Kinash, N.I.; Hevus, O.I.; Shermolovich, Yu.G.; Zaichenko, A.S. (Вiopolymers and Cell, 2018)
Aim. Purposeful preparation of polymeric surfactants combining hydrophobic fluorine-containing and hydrophilic synthetic and natural blocks via radical and non-radical reactions using peroxide, epoxide and/or amino- terminal groups of the polymeric elementary blocks. Methods. Radical and non-radical condensation reactions, polymerization, spectral (NMR- and luminescence spectroscopy), gel-permeation chromatography and other analytical techniques`. Results. Primary oligomers poly(F-MA)-MP were synthesized via radical polymerization of fluorine-alkyl methacrylate (F-MA) in the presence of peroxide-containing telogen (MP). That provides controlling the oligomer chain length and architectures as well as entering a terminal peroxide group in the macromolecules. Radical polymerization of vinyl pyrrolidone (NVP) initiated by poly(F-MA)-MP as macroinitiator in the presence of epoxide-containing derivative of cumene (CGE) was used for obtaining water soluble poly(F-MA)-block-poly(NVP)-CGE. Finally oligonucleotide (ONC) was attached via condensation reaction of ONC primary amino group with terminal epoxide group of poly(F-MA)-block-poly(NVP)-CGE. Conclusions. A series of novel block/comb-like copolymers with synthetic and natural parts was synthesized. Obtained tri-block copolymers can be used as markers for labeling bacteria and pathological items including cancer cells.